Ramainya Pasar Sosiologi (Berebut Menafsirkan Realitas Sosial) - Dadi Nurhaedi (Jurnal Sosiologi Reflektif, 2014)
This article explains the variety and the struggle of thoughts among sociologist in interpretating social reality. They have been trying to provide an interpretatiobn about the social reality. Negotiations to fid the truth of knowledge of social reality have been constanly going on without a satisfying agreement. Just like a business, it seems that someone who possesses an authority has bequeathed (his assets) as a capital for the survival of sociology market.